PENGEMBANGAN MEDIA KOMIK PADA MATERI INDONESIAKU KAYA BUDAYA TOPIK KEKAYAAN BUDAYA INDONESIA BERBANTU POWERPOINT DI SD NEGERI 101921 BERINGIN - Sari, Vira Cantika; Fitrah Dwi, Dara (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research aims to develop comic media assisted by powerpoint on the material of Indonesiaku Kaya Budaya, the topic of cultural wealth that is suitable for use in the learning process in grade IV of elementary school. This research is a type of development research using the ADDIE development model up to the evaluation stage. The instrument data is a questionnaire or questionnaire given to several material expert validators, language expert validators, media expert validators, and teacher response validators. Based on the validation results from the material expert validator, a score of 76 was obtained with the criteria of